Rhabdomyolysis, renal failure, and visual loss under BRAF/MEK inhibitors trametinib and dabrafenib - Finsterer, Josef (Revista Médica de Chile, 2020)
MEK- and BRAF-inhibitors trametinib and dabrafenib are successfully used for BRAF-mutated, metastasizing melanoma, but these compounds may induce side effects. We report a 50 years old female with BRAF-mutated metastasizing melanoma who received trametinib (2mg/d) and dabrafenib (200mg/d) after using interferon without results. Shortly after starting trametinib/dabrafenib, she experienced an inability to abduct the left eye. Eight days after starting this therapy the patient experienced loss of appetite, vomiting, diarrhea, vertigo, and fever of 40°C. Two days later she experienced visual loss, requiring permanent support for her daily activities. Two further days later myoglobinuria appeared in the absence of myalgias or muscle weakness but accompanied by marked tiredness and inactivity. She could not eat or drink during four days prior to admission. The patient suspected an adverse effect of trametinib/dabrafenib and discontinued it 2 days prior to admission, Thereafter, she experienced an almost complete remission of the deficits except for ocular muscle weakness and visual impairment.